A 9‐year, bidirectional prospective analysis of depressive symptoms and adiposity: The African American Health Study. (13th November 2014) - Hawkins, Misty A.W.; Miller, Douglas K.; Stewart, Jesse C.
<x xml:space="preserve">Abstract</x> Objective Depression may be a predictor and consequence of obesity. However, available evidence for racial minorities has been inconsistent, and more prospective studies are needed. Thus, this study's objective was to examine whether depressive symptom severity is a predictor and/or consequence of total adiposity over a 9‐year period in a representative sample of late middle‐aged African‐Americans. Methods A total of 410 participants (aged 49–65 years; baseline) in the prospective cohort African American Health study were examined. Depressive symptom severity was assessed with the Center for Epidemiologic Studies‐Depression Scale (CES‐D). Total body fat percent (BF%) and body mass index (BMI; kg/m2) were assessed. Structural equation models were tested. Results All model fit statistics, other than χ2, indicated good fit (RMSEA ≤ 0.058, SRMR ≤ 0.052, CFI ≥ 0.95). Baseline CES‐D did not predict 9‐year changes in BF% (β = −0.01, P = 0.78) or BMI (β = −0.01, P = 0.77). Baseline BF% (β = 0.05, P = 0.39) and BMI (β = 0.08, P = 0.095) did not predict 9‐year change in CES‐D. Conclusions Depressive symptom severity was not a predictor or consequence of excess total adiposity in late middle‐aged African‐American adults. Including a depression module in obesity prevention and treatment programs specifically designed for late middle‐aged African‐Americans may not have a beneficial effect on obesity outcomes.